Silicosis as a predictor of tuberculosis mortality and treatment failure and need for incorporation in differentiated TB care models in India - Mihir P. Rupani (BMC, 2023)
Abstract Background Differentiated tuberculosis (TB) care is an approach to improve treatment outcomes by tailoring TB management to the particular needs of patient groups based on their risk profile and comorbidities. In silicosis-prone areas, the coexistence of TB and silicosis may exacerbate treatment outcomes. The objective of the study was to determine predictors of TB-related mortality, treatment failure, and loss to follow-up in a silicosis-prone region of western India. Methods A retrospective cohort was conducted among 2748 people with TB registered between January 2006 and February 2022 in Khambhat, a silicosis-prone block in western India. Death, treatment failure, and loss to follow up were the outcome variables. The significant predictors of each outcome variable were determined using multivariable logistic regression and reported as adjusted odds ratios (aOR) with 95% confidence intervals (CIs). Results In the cohort of 2,748 people with TB, 5% presented with silicosis, 11% succumbed to the disease, 5% were lost to follow-up during treatment, and 2% encountered treatment failure upon completion of therapy. On multivariable logistic regression, concomitant silicosis [aOR 2.3 (95% CI 1.5-3.5)], advancing age [aOR 1.03 (95% CI 1.02-1.04)], male gender [aOR 1.4 (95% 1.1-1.9)], human immunodeficiency virus (HIV) positive [aOR 2.2 (95% 1.02-4.6)], and previous TB treatment [aOR 1.5 (95% CI 1.1-1.9)] significantly predicted mortality among people with TB. Concomitant silicosis [aOR 3 (95% CI 1.4-6.5)], previous TB treatment [aOR 3 (95% CI 2-6)], and multi-drug resistant TB [aOR 18 (95% CI 8-41)] were the significant predictors of treatment failure on adjusted analysis. Advancing age [aOR 1.012 (1.001-1.023)], diabetes [aOR 0.6 (0.4-0.8)], and multi-drug resistance [aOR 6 (95% CI 3-12)] significantly predicted loss to follow-up after adjusting for confounders. Conclusions Controlling silicosis might decrease TB mortality and treatment failure in silicosis-prone regions. The coexistence of HIV and silicosis may point to an increase in TB deaths in silicosis-prone areas. Silicosis should now be acknowledged as a major comorbidity of TB and should be included as one of the key risk factors in the differentiated TB care approach. Primary care physicians should have a high clinical suspicion for silicosis among individuals diagnosed with TB in silicosis-prone blocks.